A quantitative genetic analysis of the effect of crossbreeding on the growth rate of the South African abalone, Haliotis midae - Vorster, Gysbert (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2003.